Pengaruh Penerapan Model Project Based Learning Terhadap Hasil Belajar Siswa pada Mata Pelajaran Biologi Kelas X di SMA Negeri 1 Sutera - Mailanda, Aqsa; Hidayati, Abna; Zen, Zelhendri; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article discusses the effect of the application of the Project Based Learning (PBL) model on student learning outcomes in biology subjects. The research method used is quantitative with a quasi-experimental design. This research was conducted in a high school by involving a group of students who were divided into two groups, namely an experimental group that applied the PBL model and a control group that used conventional methods. The instruments used are tests, observations, and questionnaires. The resulting data was analyzed using descriptive statistical tests and t-tests. The results showed that the application of PBL significantly improved students' understanding of biology concepts, critical thinking skills, and learning motivation. These findings indicate that PBL can be an effective alternative in teaching biology, increasing student engagement, and resulting in more meaningful learning